Laurus nobilis L. Essential Oil-Loaded PLGA as a Nanoformulation Candidate for Cancer Treatment - KARTAL, MURAT; ERCİN, ESİN; KECEL, SERDA GÜNDÜZ; GOK, BAHAR; AYDIN, TUĞBA; BUDAMA, Yasemin; KARTAL, MURAT (My University, 2022)
The aim of this study was to obtain essential oil (LNEO) from the Laurus nobilis L. plant, and to prepare LNEO-loaded poly lactic-co-glycolic acid (PLGA) nanoparticles (NPs) as an approach in cancer treatment. The components of the obtained LNEO were analyzed using GC-MS. The LNEO-NPs were synthesized by the single-emulsion method. The LNEO-NPs were characterized using UV-Vis spectrometry, Dynamic Light Scattering (DLS), Scanning Electron Microscopy (SEM), and a DNA binding assay, which was performed via the UV-Vis titration method. According to the results, the LNEO-NPs had a 211.4 +/- 4.031 nm average particle size, 0.068 +/- 0.016 PdI, and -7.87 +/- 1.15 mV zeta potential. The encapsulation efficiency and loading capacity were calculated as 59.25% and 25.65%, respectively, and the in vitro drug release study showed an LNEO release of 93.97 +/- 3.78% over the 72 h period. Moreover, the LNEO was intercalatively bound to CT-DNA. In addition, the mechanism of action of LNEO on a dual PI3K/mTOR inhibitor was predicted, and its antiproliferative activity and mechanism were determined using molecular docking analysis. It was concluded that LNEO-loaded PLGA NPs may be used for cancer treatment as a novel phytotherapeutic agent-based controlled-release system.
Keywords: DNA binding; PLGA; controlled release system; laurel essential oil; nanoparticle